Math quiz why do men predominate. - Patel, P. (IEEE spectrum)
No woman has yet won one of the three top mathematics awards- the Fields, the Abel, or the Wolf. It's part of what's often called the math gender gap, which in the United States starts early-at least twice as many boys as girls score in the 99th percentile on state level math assessment tests.